2017
DOI: 10.22270/jddt.v7i6.1538
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optimization of Novel Glipizide Sustained Release Matrices for Solubility and Dissolution Enhancement by Solid Dispersion Through Hydrophillic Carriers

Abstract: The present research work was to improve the dissolution rate of glipizide which belongs to BCS II drug by enhancing its aqueous solubility using different hydrophilic carriers like PEG 6000 and hydroxylpropyl methylcellulose E15 (HPMC E15). The solid dispersion was embedded into the matrix of polymers to sustain the release pattern of drug. The various solid dispersion formulations were prepared by employing fusion method using different carriers. Further solid dispersion formulations were subjected to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…after solubility experiments/equilibrium. The T fus value of GLZ was determined as 484.60 K by Dash et al 3 Choudhary et al determined the T fus value of GLZ as 478.20 K. 18 Shende and Fiske found the T fus value of GLZ as 489.28 K. 19 The determined T fus value of GLZ at 484.21 K in the proposed study was very close to that reported by Dash et al 3 1. The solubility of GLZ in water has been reported by many researchers.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…after solubility experiments/equilibrium. The T fus value of GLZ was determined as 484.60 K by Dash et al 3 Choudhary et al determined the T fus value of GLZ as 478.20 K. 18 Shende and Fiske found the T fus value of GLZ as 489.28 K. 19 The determined T fus value of GLZ at 484.21 K in the proposed study was very close to that reported by Dash et al 3 1. The solubility of GLZ in water has been reported by many researchers.…”
supporting
confidence: 77%
“…The solubility, dissolution, and eventually the bioavailability of GLZ can be improved by different techniques such as development of liquisolid tablets by using poly­(ethylene glycol)-400 (PEG-400) as a liquid vehicle, polymeric microparticles, , polymeric nanoparticles, co-solvent solubilization approach, complexation of GLZ with α and β-cyclodextrins, solid self-nanoemulsification, microemulsion technology, , preparation of osmotically controlled oral drug-delivery system, solid dispersion, nanosuspension, microwave-generated bionanocomposites, transdermal drug-delivery system, floating bioadhesive drug-delivery system, and microcrystallization . The solubility data of GLZ in various neat solvents (NS) are scarce in research database.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that SD is the dispersion of one or more active ingredients in a carrier or matrix in a solid state. There are various methods for obtaining SD, which can be divided into the following [5]: Usually, SD are widely used in medicine [6][7][8][9][10], because these systems can provide many additional advantages:…”
Section: Solid Dispersions: Methods Of Preparation Properties Applimentioning
confidence: 99%
“…Usually SD are widely used in medicine [6][7][8][9][10], because these systems can provide many additional advantages: 1. to increase the solubility of poorly soluble drugs, thereby increasing the rate of dissolution, absorption and bioavailability. 2. to improve the drug output of ointments creams and gels.…”
Section: Solid Dispersions: Methods Of Preparation Properties Applimentioning
confidence: 99%